The Role Of Higher Education Services In The Welfare Of The Country's Population: Peran Layanan Pendidikan Tinggi dalam Kesejahteraan Penduduk Negara - Mirzakhadjaeva Shahzoda Shukhratovna (Academia Open, 2025)
General Background: Higher education services are recognized as key drivers of human capital formation, innovation, and socio-economic progress. Specific Background: In Uzbekistan, ongoing reforms such as curriculum modernization, institutional expansion, and international partnerships highlight the state’s prioritization of higher education in improving societal well-being. Knowledge Gap: However, limited empirical insight exists on how higher education services translate into measurable welfare outcomes, such as employment, income, social participation, and life expectancy. Aim: This study investigates the economic and social significance of higher education services in shaping population welfare, with emphasis on their efficiency, labor market implications, and contribution to sustainable development. Results: Findings reveal that higher education fosters job creation, increases income, enhances innovation, and improves quality of life. Comparative evidence also demonstrates that developed countries with robust higher education systems enjoy higher life expectancy and lower unemployment. Novelty: The study introduces methodological approaches combining GDP share, employment rates, investment levels, and life expectancy indicators to systematically measure the welfare impact of higher education. Implications: The results underscore that advancing Uzbekistan’s higher education system in line with international standards and principles of social justice is essential for strengthening human capital, sustaining economic growth, and ensuring long-term population welfare.Highlight : Higher education directly supports income, jobs, and living standards. It enhances innovation, social activity, and sustainable growth. Strong education systems align with higher life expectancy and lower unemployment. Keywords : Higher Education Services, Population Welfare, Human Capital, Education System, Economic Efficiency